2016
DOI: 10.1115/1.4034901
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Evaluation of the Dependence of Pool Boiling Heat Transfer Enhancement on Sintered Particle Coating Characteristics

Abstract: Immersion cooling strategies often employ surface enhancements to improve the pool boiling heat transfer performance. Sintered particle/powder coatings have been commonly used on smooth surfaces to reduce the wall superheat and increase the critical heat flux (CHF). However, there is no unified understanding of the role of coating characteristics on pool boiling heat transfer enhancement. The morphology and size of the particles affect the pore geometry, permeability, thermal conductivity, and other characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 38 publications
(11 citation statements)
references
References 33 publications
(48 reference statements)
1
8
0
Order By: Relevance
“…24,80,81 As such, a lot of efforts have been devoted to enhancing nucleate boiling heat transfer efficiency (before the CHF) and delaying the occurrence of boiling crisis, i.e., increasing CHF, through manipulating bubble behaviors using micro/nanostructures. 6,58,60,[82][83][84][85][86][87][88][89][90][91][92][93][94] Compared with the plain surface, micro/ nanostructured surfaces can decrease the ONB, improve the HTC, and increase the CHF in nucleate boiling heat transfer regime (Figure 2A). [61][62][63]82,[95][96][97][98][99][100] The underlying mechanisms for the enhancements have been attributed to the increased nucleation site density for efficient liquid vaporization, increased solid-liquid interface for sufficient heat transfer area, and enhanced capillary pumping for rapid liquid supply.…”
Section: Context and Scalementioning
confidence: 99%
“…24,80,81 As such, a lot of efforts have been devoted to enhancing nucleate boiling heat transfer efficiency (before the CHF) and delaying the occurrence of boiling crisis, i.e., increasing CHF, through manipulating bubble behaviors using micro/nanostructures. 6,58,60,[82][83][84][85][86][87][88][89][90][91][92][93][94] Compared with the plain surface, micro/ nanostructured surfaces can decrease the ONB, improve the HTC, and increase the CHF in nucleate boiling heat transfer regime (Figure 2A). [61][62][63]82,[95][96][97][98][99][100] The underlying mechanisms for the enhancements have been attributed to the increased nucleation site density for efficient liquid vaporization, increased solid-liquid interface for sufficient heat transfer area, and enhanced capillary pumping for rapid liquid supply.…”
Section: Context and Scalementioning
confidence: 99%
“…The effect of particle size in sintered coatings on pool boiling behavior has been extensively studied in the literature [19,20]. In addition, there have been detailed characterizations and statistical descriptions of sintered wick structures [21], and their effects on pool boiling [22]. However, few studies have addressed the effect of particle size during capillary-fed boiling; moreover, the wick types, heating area, and wick thicknesses differ between each of these studies.…”
Section: Single-layer Wicks Testing: Effect Of Sintered Particle Sizementioning
confidence: 99%
“…Experimental studies have shown that nanoscale surface roughness affects the meniscus profile and heat transfer rate in thin film evaporation [6]. For larger structures, e.g., hoodoo structures [7], micropillars [8], sintered mesh [9], sintered microparticles [10], and hierarchical structures [11], local roughness at the contact line also plays a role in determining heat transfer rate. In order to design surface structures that provide further heat transfer enhancement, it is of fundamental significance to understand the heat transfer characteristics of the evaporating meniscus on rough surfaces.…”
Section: Introductionmentioning
confidence: 99%